Education-Based Community Service Through Introduction to Marine Biota Using Teaching Aids at TK RA Ar-Rahman in Ujong Tanoh Darat, Meureubo District - Hayatun Nufus; Sri Wahyuni; Asri Mursawal; Ika Kusumawati; Mai Suriani; Samsul Bahri; Rika Astuti; Nurul Najmi; Arung Samudra; Anisa Mardhatila (Marine Kreatif, 2026)
Early childhood is a strategic target group for introducing environmental knowledge and awareness from an early age. One important aspect that needs to be introduced is marine biodiversity as an essential component of ecosystems that play a vital role in sustaining life. However, learning about marine organisms at the kindergarten level is generally limited and still relies on conventional media, resulting in a lack of concrete and interactive learning experiences. This community service activity aimed to improve the knowledge and awareness of students at TK RA Ar-Rahman, Ujong Tanoh Darat Village, Meureubo District, West Aceh Regency, regarding marine organisms through educational activities using teaching aids. The methods applied included interactive lectures, demonstrations using teaching aids, question-and-answer sessions, and educational games. The activity was conducted on January 22, 2026, involving students aged 4–6 years as the main participants. The results showed an increase in students’ understanding of various types of marine organisms and the development of positive attitudes toward the importance of marine environmental conservation. In addition, the use of teaching aids was proven to enhance students’ learning interest and active participation during the learning process. In conclusion, this activity is effective as a model of environmental education for early childhood and has the potential to be replicated in other schools with similar characteristics.